Natural Based Carbon Briquettes: The Effect of Coffee Ground Carbonization Temperatures as Renewable Energy Alternative - Fauziah Ramadhani; Ghina Nabila Nur Sa’diyyah; Salsabila Azaliyah Putri; Danisa Dwi Anggraeni; Alfiana Adhitasari; Saripudin Saripudin (Journal of Green Science and Technology, 2025)
Coffee consumption in Indonesia has been increasing over time. As a result of the high consumption and production, coffee waste often ends up in landfills. One potential solution to this problem is converting coffee waste into reusable products. Coffee grounds waste can be utilized as renewable energy in the form of briquettes. In this research, coffee grounds are used as briquette material. Briquettes are made by the carbonization method. Temperature plays a crucial role in determining the quality of briquette. This study aims to identify the optimum carbonization temperature, with variations of 350°C, 400°C, and 450°C. Each briquette sample was analyzed according to the Indonesian National Standard SNI 01-6235-2000. The results show that all carbonization temperatures produced briquettes with high calorific values (>5000 cal/g), that is 6981 cal/g at 350°C, 7037 cal/g at 400°C, and 7043 cal/g at 450°C. However, the resulting briquettes did not meet the standard criteria for density, fixed carbon, and volatile matter.